EFFECT OF BASTI KARMA IN GRIDHRASI-A CASE STUDY - Sanjana B. Pednekar; V.J. Tiwari; Amit Chavan (International Journal of Ayurveda and Pharma Research, 2020)
Gridhrasi is one of the Nanatmajavyadhis of Vatadosha. The term Gridhrasi indicates the typical gait that resembles of Gridhra i.e. vulture. Ruka (pain), Toda (pricking sensation), Stambha (stiffness) in waist, hip, back of the thigh, knee, calf and foot respectively are the main symptoms. Gridhrasi can be correlated with sciatica in modern science. Improper sitting posture, continuous and over exertion, jerking movements produce structural abnormality in spine may cause sciatica. A 48 years old female patient approached the OPD with radiating pain from lumbar region to left lower limb and difficulty in walking since one year and was diagnosed with Gridhrasi. As Gridhrasi is Vatajavyadhi, Basti is the best treatment for Gridhrasi. Hence for this patient line of treatment was Sarvangaabhyanga with Sahachartail, Sarvangabashpaswed with Dashamoolkwath, Basti in the form of Erandmooladiniruhabasti and Sahachar tail Anuvasanbasti followed by Panchatikta ksheer basti with Guggultikta ghrut is chosen here along with some oral medications Sahacharadikashay Ghana vati, Prasarnyadikashay Ghana vati, Vishatindukvati, Guggultiktakashay was given. This treatment provided marked improvement in signs and symptoms of Gridhrasi. Before treatment Ruka was 4, Aruchi was 1, Toda was 3, Stambha was 4, Gaurav was 2, Spandana was 2, SLRT left side was 4 and right side was 1, walking distance was 3 which turns after treatment to 2,0,1,0,1,1,0, left side-1, right side-0,1 respectively.